2015
DOI: 10.1103/physrevb.92.134408
|View full text |Cite
|
Sign up to set email alerts
|

Localized itinerant electrons and unique magnetic properties ofSrRu2O6

Abstract: SrRu2O6 has unique magnetic properties. It is characterized by a very high Néel temperature, despite its quasi-two-dimensional structure, and has a magnetic moment more than twice reduced compared to the formal ionic count. First principles calculations show that only an ideal Néel ordering in the Ru plane is possible, with no other metastable magnetic solutions, and, highly unusually, yield dielectric gaps for both antiferromagnetic and nonmagnetic states. We demonstrate that this strange behavior is the resu… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
65
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(73 citation statements)
references
References 20 publications
7
65
0
1
Order By: Relevance
“…In the ionic approximation the energy gain is of the order of E E1u − E E2g ≈ 2t ′ 1 . Interestingly, the long range Neél antiferromagnetic (AFM) order does not destroy MOs, but even increases this energy gain [8]. These are the reasons why the MOs are so clearly seen in the band structure calculations in SrRu 2 O 6 [8].…”
Section: Pacs Numbersmentioning
confidence: 94%
See 1 more Smart Citation
“…In the ionic approximation the energy gain is of the order of E E1u − E E2g ≈ 2t ′ 1 . Interestingly, the long range Neél antiferromagnetic (AFM) order does not destroy MOs, but even increases this energy gain [8]. These are the reasons why the MOs are so clearly seen in the band structure calculations in SrRu 2 O 6 [8].…”
Section: Pacs Numbersmentioning
confidence: 94%
“…In real materials t ′ 1 /3 ∼ −t ′ 2 > 0 and the two highest MO levels, A 1g and E 1u , turn out to be nearly degenerate [8,13]. This is conducive for the spin-orbit coupling (SOC) and is the reason why the SOC is so efficient in the case of one t 2g hole as in α−RuCl 3 or in Na 2 IrO 3 .…”
Section: Pacs Numbersmentioning
confidence: 99%
“…As it was shown theoretically, quantum fluctuations may stabilize a quantum spin liquid (SL) phase between a state of massless Dirac fermions and an antiferromagnetically ordered insulating phase [18]. Moreover, many other exotic phases may appear in the system with the honeycomb lattice: an unusual Z 2 SL state, phase with quasi-molecular orbitals formed on the hexagons, incommensurate Néel order, a dimerized state with spontaneously broken rotational symmetry, a valence bond liquid and lattice nematic phases, columnar dimer order with a non-bipartite structure, etc [19][20][21][22][23][24][25][26][27][28][29][30].…”
Section: Introductionmentioning
confidence: 99%
“…The situation observed here that the linear combination of Os t 2g orbitals on different sites plays a crucial role in understanding the band structure and the realized physical properties reminds us a recent molecular-orbital picture proposed to apply to SrRu 2 O 6 for explaining its small magnetic moment [34]. Although our choice of the unit cell and the basis orbitals, t 2g orbitals on two Os sites, is different from theirs, hexagonal molecular orbitals on six Ru sites, it is interesting that the intersite hopping among the extended 4d or 5d orbitals is essential to realize the fascinating physics, topological properties and magnetism, in these materials.…”
Section: Resultsmentioning
confidence: 99%
“…Theoretical studies of this compound suggested that the strong hybridization between Ru and O ions is responsible for this unique character [31,33]. Formation of molecular orbitals within a Ru hexagonal plane owing to such a strong hybridization was also pointed out to explain the small magnetic moment [34]. However, under a certain pressure or strain, band inversion is induced at one of the time-reversal invariant momenta (TRIM), resulting in a non-trivial band topology.…”
Section: Introductionmentioning
confidence: 99%